Breaking the rules - Bradford, Barbara Taylor, 1933- (New York : St. Martin's Press, 2009)
When a psychopath with deadly intent vows to shatter M's world forever, the muse and star model to France's iconic designer Jean-Louis Tremont will break the rules to protect her family and her life.
Keywords: Models (Persons) -- Fiction; Celebrities -- Fiction; Stalkers -- Fiction; Domestic fiction; Suspense fiction